Análisis del liderazgo como habilidades gerenciales y su efecto en el crecimiento de las Empresas Textiles en la ciudad de Quito, desde el 2008 hasta 2012 - Mejía Velásquez, Pablo Iván (2014)
The purpose of this research is to conduct an analysis of leadership as general ability in the textile company Quito to establear leadership and more incidents factors on growth of the company . It took no probabilistic formed with 4 textile companies such as Prisma Home, Profitex , Textile and Modetex Ecuador , with a sample consisting of 80 subjects between managers or heads of areas and subordinate. To analyze the leadership conducted two surveys one to determine the kind of leadership most used by these organizations the instrument used was the MLQ five short form , along with a survey of labor satisdación developed by Bittel (1985 )